(untitled) (Research, Society and Development, 2023)
Ants lead the space of beings considered as the most evolved, insects endowed with an extraordinary capacity to adapt to any environment, with survival strategies based on a division of labor between the colony, which attracts attention to several research and scientific discoveries. Thus, the work aimed to observe the feeding behavior of ants in domestic environments in the cities of Arapiraca and Major Isidoro, in Alagoas, through the offer of attractants: honey, sugar and formitol (insecticide) as baits. Traps were made in the form of “ribbons” with different sizes (10cm, 12cm and 20cm) on smooth surfaces and different turns to attract them. By observing the behavior of ants, three different species of ants were identified at the research sites: Ghost ant (Tapinoma Melanocephalu); Crazy Ant (Paratrechina longicornis) and Argentinean Ant (Linepithema humilfe). The latter appeared in greater quantity (64.4%) of the 414 individuals identified in total. Ants had a higher rate of permanence and number of individuals in the night shift, the time and quantity rates were moderate in the afternoon shift, and a lowest permanence rates and quantity were in the morning shift. It was concluded that the purpose of the study was achieved, according to the observations made through the variables (the environment, the identification of species, the ants’ food preference and the estimation of the time spent around the food).